Synthesis of Mg and Zn diolates and their use in metal oxide deposition12. Issue 19 (5th April 2019) - Frenzel, Peter; Preuß, Andrea; Bankwitz, Jörn; Georgi, Colin; Ganss, Fabian; Mertens, Lutz; Schulz, Stefan E.; Hellwig, Olav; Mehring, Michael; Lang, Heinrich
Abstract : Mg and Zn containing precursors for the generation of metal oxide layers by CVD and/or spin-coating are described. Abstract : The synthesis of complexes [M(OCHMeCH2 NMeCH2 )2 ] (5, M = Mg;7, M = Zn) is described. Treatment of MeHNCH2 CH2 NMeH (1 ) with 2-methyloxirane (2 ) gave diol (HOCHMeCH2 NMeCH2 )2 (3 ), which upon reaction with equimolar amounts of MR2 (4, M = Mg, R = Bu;6, M = Zn, R = Et) gave5 and7 . The thermal behavior and vapor pressure of5 and7 were investigated to show whether they are suited as CVD (= chemical vapor deposition) and/or spin-coating precursors for MgO or ZnO layer formation. Thermogravimetric (TG) studies revealed that5 and7 decompose between 80–530 °C forming MgO and ZnO as evidenced by PXRD studies. In addition, TG-MS-coupled experiments were carried out with7 proving that decomposition occurs by M–O, C–O, C–N and C–C bond cleavages, as evidenced from the detection of fragments such as CH4 N +, C2 H4 N +, C2 H5 N +, CH2 O +, C2 H2 O + and C2 H3 O + . The vapor pressure of7 was measured at 10.4 mbar at 160 °C, while5 is non-volatile. The layers obtained by CVD are dense and conformal with a somewhat granulated surface morphology as evidenced by SEM studies. In addition, spin–coating experiments using5 and7 as precursors were applied. The corresponding MO layer thicknesses are between 7–140 nm (CVD) or 80 nm and 65 nm (5, 7 ; spin-coating). EDX and XPS measurements confirm the formation of MgO and ZnO films, however, containing 12–24 mol% (CVD) or 5–9 mol% (spin-coating) carbon. GIXRD studies verify the crystalline character of the deposited layers obtained by CVD and the spin-coating processes.